Mechanical fragmentation vs. electrodynamic pulse disaggregation for weak acid leach sample preparation: Implications for the exploration of unconformity-hosted uranium deposits. (March 2022) - Pilsworth, Collette; Layton-Matthews, Daniel; Leybourne, Matthew I.; Voinot, Alexandre; Chipley, Donald
Abstract: The introduction of electrodynamic pulse disaggregation (EPD) as a sample preparation tool, traditionally dominated by mechanical (jaw-crusher) fragmentation (MF), begs the need for a comparison of element concentrations and isotopic ratios results from leaching of samples prepared by each of these methods. With this in mind, element concentrations and Pb isotope ratios were measured for samples from the Cigar Lake unconformity-hosted uranium deposit, Athabasca Basin, Canada using a weak acid leach (2% HNO3 ) digestion. Six sample preparation methods (SPMs) were established from MF and EPD: SPM1) MF samples sieved to 0.5–1.18 mm; SPM2) MF samples sieved to > 1.18 mm, shaken with DI water to extract a clay-rich water, clay-rich water dried; SPM3) dried aliquot of water after EPD; SPM4) < 2 μm clay-sized mineral fraction separated from settled EDP water; SPM5) EPD samples sieved to < 0.5 mm; and SPM6) EPD samples sieved to 0.5–1.18 mm. Pathfinder elements for unconformity-hosted uranium deposits (U, Pb, Th, Ni, Co, As, Cu, and Zn) show increasing concentrations with SPMs that produced a higher portion of the clay-sized mineral fraction, up to 15.92 μg/g U, 40.91 μg/g Th, and 4.85 μg/g Pb. Sample preparation methods 1, 2, and 4 have the most radiogenic Pb isotope ratios ( 207 Pb/ 206 Pb = 0.10–0.40), with least radiogenic ratios in other SPMs ranging from 207 Pb/ 206 Pb = 0.23 to 0.82. The 207 Pb/ 206 Pb values, combined with 206 Pb/ 204 Pb and 207 Pb/ 204 Pb, indicate that an increase in common Pb has diluted the radiogenic components for the least radiogenic fractions. MF and EPD both offer benefits for preparing samples for weak acid leach but results from this study show that clay extracted by EPD (SPM4) is the optimal method, producing higher pathfinder element contents and radiogenic Pb values. This study demonstrates that SPMs can result in variable mixes of the original minerals, which affects element concentrations and Pb isotope ratios that are extracted. The modification of geochemical results via SPMs, with the leaching of common Pb unrelated to ore system processes and changes to pathfinder elements concentrations, has implications for using weak acid leach and other partial leaches in exploration in sandstone hosted systems for all mineral commodities. The generation of unreliable geochemical results decreases the effectiveness of exploration programs, potentially missing positive anomalies and overall increases the cost associated with ore deposit discovery, offsetting the added costs of SPMs for geochemical surveys. Highlights: Mechanical fragmentation and electrodynamic pulse disaggregation sample preparation methods for weak acid leach (2% HNO3 ). Sample preparation methods can affect element concentrations and Pb isotope ratios that are extracted by weak acid leach. Clay extracted by electrodynamic pulse disaggregation is the optimal method for unconformity-hosted uranium exploration programs.